Deferred Prosecution Agreement for Corporations: A Study of the Relevance of Article 328 of the Criminal Procedure Code from the Perspective of Substantive Justice - Noviar Haikal Prasetya; Muhammad Nurcholis Alhadi; Uut Rahayuninsih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The enactment of Article 328 of Law Number 20 of 2025 concerning the Criminal Procedure Code marks a paradigm shift in corporate criminal law enforcement by introducing the Deferred Prosecution Agreement (DPA) mechanism. This mechanism shifts the resolution of corporate criminal cases from the conventional criminal justice model toward a settlement based on an agreement between the Public Prosecutor and the corporation. However, the regulation raises concerns regarding the mechanism's ability to achieve substantive justice, particularly concerning the scope of prosecutorial discretion, judicial oversight, and the recovery of unlawfully obtained profits. This research aims to analyze the juridical implications of this paradigm shift on the realization of substantive justice and to formulate a regulatory framework for DPAs by strengthening judicial oversight mechanisms and disgorgement standards. This is a normative legal study employing statutory, conceptual, and comparative approaches. The analysis is prescriptive in nature, grounded in the Theory of Substantive Justice. The findings indicate that the DPA regulation in Article 328 of the New Criminal Procedure Code does not yet fully guarantee the realization of substantive justice, as it fails to adequately regulate judicial oversight mechanisms or establish objective and measurable disgorgement standards. These weaknesses risk creating disparities in legal application, diminishing the deterrent effect on corporations, and reducing the effectiveness of recovering losses suffered by the state and victims.